2004
DOI: 10.1177/0363546503258911
|View full text |Cite
|
Sign up to set email alerts
|

Relative Balance of Serratus Anterior and Upper Trapezius Muscle Activity during Push-Up Exercises

Abstract: Clinical selection of exercises for improving scapular control should consider both maximum serratus activation and upper trapezius/serratus anterior ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
304
6
22

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(337 citation statements)
references
References 19 publications
5
304
6
22
Order By: Relevance
“…EMG was recorded from the lower serratus anterior division as described by Ludewig and Cook (2000). The results of the present study are in agreement with previous authors that have suggested the lower division produces upward rotation (Ludewig et al, 2004;Roren et al, 2013) and controls downward rotation The authors suggest posterior tilt is produced by the inferior laterally directed fibers of the lower division and the middle division is likely to contribute to controlling anterior tilt too by keeping the medial border close to the thoracic spine. Further research is needed to explore the degree of muscle activity for each serratus anterior subdivision during a variety of rehabilitation exercises.…”
Section: Discussionsupporting
confidence: 93%
“…EMG was recorded from the lower serratus anterior division as described by Ludewig and Cook (2000). The results of the present study are in agreement with previous authors that have suggested the lower division produces upward rotation (Ludewig et al, 2004;Roren et al, 2013) and controls downward rotation The authors suggest posterior tilt is produced by the inferior laterally directed fibers of the lower division and the middle division is likely to contribute to controlling anterior tilt too by keeping the medial border close to the thoracic spine. Further research is needed to explore the degree of muscle activity for each serratus anterior subdivision during a variety of rehabilitation exercises.…”
Section: Discussionsupporting
confidence: 93%
“…In cooperation with the lower trapezius, these muscles are optimally positioned to keep the scapula aligned with the thorax and ensure dynamic stabilization. Shoulder disorders are observed to be associated with an abnormal activation pattern of these muscles, termed scapular muscle imbalance 5) . Specifically, patients with neck and shoulder disorders frequently show excessive activity of the upper trapezius combined with reduced activity of the lower trapezius and serratus anterior muscles 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder disorders are observed to be associated with an abnormal activation pattern of these muscles, termed scapular muscle imbalance 5) . Specifically, patients with neck and shoulder disorders frequently show excessive activity of the upper trapezius combined with reduced activity of the lower trapezius and serratus anterior muscles 5) . Scapular setting exercises are used to stabilize the shoulder and are of two types: open kinetic-chain (OKC) and closed kinetic-chain (CKC) exercises.…”
Section: Introductionmentioning
confidence: 99%
“…And it was reported that the combination of standard rehabilitation interventions and scapulothoracic joint control training exercises were an effective treatment of the shoulder joint dysfunction [11,12]. Therefore, research on exercises to change scapular muscle activity [13,14] has led to the recognition of the importance of scapular stability for shoulder movement in normal scapular muscle activity. However, apart from shoulder elevation, the mechanism of scapular stability, especially in isometric contraction and movement of the shoulder joint, remains unknown.…”
Section: Introductionmentioning
confidence: 99%